2019
DOI: 10.1177/0706743719878987
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mental Disorders and Suicidality in Canadian Provinces

Abstract: Objective: There is limited information to guide health-care service providers and policy makers on the burden of mental disorders and addictions across the Canadian provinces. This study compares interprovincial prevalence of major depressive disorder (MDD), bipolar disorder, generalized anxiety disorder (GAD), alcohol use disorder, substance use disorders, and suicidality. Method: Data were extracted from the 2012 Canadian Community Health Survey—Mental Health ( n = 25,113), a representative sample of Canadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…The prevalence of mental health disorders is well documented through epidemiological and survey data. An estimated 26–30% of the United States population is affected by a mental health disorder annually [ 102 ], while recent data using the 2012 Canadian Community Health Survey suggests that the overall prevalence of mental health disorders in those over 15 years of age was 9.59% [ 103 ]. The high prevalence of these disorders and the relatively low adherence rates [ 104 ], and limited treatment success with medications for some conditions [ 105 , 106 ], contributes to a substantial economic impact on society [ 107 ].…”
Section: Creatine and Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of mental health disorders is well documented through epidemiological and survey data. An estimated 26–30% of the United States population is affected by a mental health disorder annually [ 102 ], while recent data using the 2012 Canadian Community Health Survey suggests that the overall prevalence of mental health disorders in those over 15 years of age was 9.59% [ 103 ]. The high prevalence of these disorders and the relatively low adherence rates [ 104 ], and limited treatment success with medications for some conditions [ 105 , 106 ], contributes to a substantial economic impact on society [ 107 ].…”
Section: Creatine and Mental Healthmentioning
confidence: 99%
“…The high prevalence of these disorders and the relatively low adherence rates [ 104 ], and limited treatment success with medications for some conditions [ 105 , 106 ], contributes to a substantial economic impact on society [ 107 ]. The two most prevalent mental health disorders are depression and generalized anxiety disorder [ 103 ].…”
Section: Creatine and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce existing knowledge and practice gaps on the influence of social determinants on suicidal behaviors, inclusion of minority groups and a life span approach is imperative. An understanding of the burden of mental health will aid in the appropriate planning and allocation of mental health services (Palay et al, 2019); knowledge of the impact of membership to disadvantaged groups on suicide behaviors will assist in promoting mental health equity.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a paucity of information regarding established processes for inpatient units to allocate beds for patients with varying screening COVID-19 statuses [ 4 ]. The number of inpatient mental health beds required is dependent on the number of COVID cases and prevalence of mental illness; a previous study from our group demonstrated substantial variation in prevalence of mental disorders across provinces in Canada [ 5 ].…”
mentioning
confidence: 99%